Eyewitness: Natural disasters - Sheen, Martin; Dorling Kindersley Limited ([New York] : DK Publishing, 2009)
"When will disaster strike next? Is it true that animals can sense an impending earthquake? NATURAL DISASTERS explores the forces that shape our planet and affect our lives, from hurricanes to volcanoes. Captured on camera in the midst of turmoil, rare footage reveals the Earth at its most violent, from the lashing fury of a twister to the awesome progress of an avalanche."--Container.
Natural disasters / director Caius Julyan ; writer Anne MacLeod -- The making of Eyewitness (approx. 25 min.) / written and produced by Bill Butt ; director/cameraman, Mike Kamei -- Discover more about DK Eyewitness (approx. 2 min.).
Videodisc release of the episode from Series 3 of the British natural history TV program which originally aired in 1997.
Program content : Dorling Kindersley Ltd., c1996, 1994 (Making of Eyewitness).
Aspect ratio: 4:3.
"Also available: Eyewitness books : Natural disasters by Claire Watts"--Container insert.
A BBC Scienceworld production for BBC Worldwide Americas, Dorling Kindersley Vision in association with Oregon Public Broadcasting
Narrator: Andrew Sachs.
Keywords: Natural disasters -- Juvenile films; Storms -- Juvenile films; Volcanoes -- Juvenile films; Hurricanes -- Juvenile films; Earthquakes -- Juvenile films; Educational television programs; Nature television programs; Science television programs; DVDs for children